Indoor air quality at higher institution’s laboratory: a study on pre-symptoms, awareness and understanding among occupants - Osman, Mohamad Romizan; Azid, Azman; Juahir, Hafizan; Yunus, Kamaruzzaman; Amran, Mohammad Azizi; Mustafa, Ahmad Dasuki; Azaman, Fazureen; Mohamed Zainuddin, Syahrir Farihan (Universiti Teknologi Malaysia, 2015)
This study intends to show the effectiveness of indoor air quality (IAQ) at the higher institution laboratory. The objective is to determine the impact of current IAQ, to study the occupants’ knowledge in the indoor air pollutants and to identify the significance of occupants’ personality regarding the IAQ awareness. 100 respondents had responded to answer the questionnaires given. The questionnaires were analysed using XLSTAT2014 software for descriptive statistic and discriminant analysis in order to fulfil the outlined objectives. The finding shows that 56% of the respondents know about IAQ, while 40% and 4% did not know and not sure about the IAQ, respectively. By gender, there were 20 of male respondents having the IAQ knowledge and 21 of male respondents did not know about the IAQ. Meanwhile, 36 of female respondents have IAQ knowledge, 19 of female respondents did not know the IAQ knowledge and 4 of female respondents were not sure regarding the IAQ knowledge. Furthermore, the IAQ in the laboratory at the higher institution is considered as unhealthy based on the respondents’ complaints of their health problem symptoms. Meanwhile, the results of personality tests show that women have more IAQ awareness compared to men. It indicated that the personalities of the occupants have significance to influence and able to determine their awareness on the IAQ. Hence, it described that IAQ is a significant factor to determine and influence the health of laboratory occupants.